Analisis Kinerja Protokol Routing AODV Single Path dan Multipath Pada Jaringan IEEE 802.15.4/ ZIGBEE - Hamidi, Muhammad; Ashari, Ahmad (JISA(Jurnal Informatika dan Sains), 2018)
Routing protocol is used to keep the stabilization of connection. Its connected with the performance was caused good communication when the communication from the source node to the destination node. The main factor of success in routing protocol techniques was quality of service to provide the difference level of service in arraging and giving the traffic service prority in the the network like constant bit rate (CBR) and file transfer protocol (FTP) using wireless network sensor network (WSN).This research will analyse the achivement quality of service in IEEE 802.15.4/Zigbee network used routing protocol techniques ad hoc on demand distance vector (AODV) single path and multipath based on distance and number of nodes simulated used Cygwin software. Based on the results of tests performed using the technique of routing protocol Ad Hoc On Demand Distance Vector single path and multipath for service traffic with constant bit rate and file transfer protocol, the result packet delivery ratio and goodput better on the distance between nodes 10m than the distance between node 15m to 25m, thus indicating that the goodput affect the traffic services are used. And the average delay results using the technique of multipath routing protocol AODV lower, thus indicating that the alternative pathway suppress buffer traffic delay on the service used.